Approaches to Forming Positive Behavior in Children at Bina Anak Sholeh Kindergarten - Rifkah Rofidah; Ifa Aristia Sandra E (Universitas PGRI Madiun, 2026)
Early childhood behavior often reflects a strong sense of curiosity and boundless exploration, which sometimes poses challenges for teachers. This study aims to explore the teacher's approach to fostering positive behavior in early childhood through a case study analysis of a child in Kindergarten A at Bina Anak Sholeh Kindergarten, Tuban. This student has a habit of grabbing his teacher's shirt or skirt, requiring special treatment to correct this behavior. Using a descriptive qualitative method and a case study approach, data were collected through direct observation, interviews with the teacher, and documentation analysis. The findings indicate that a personalized approach involving direct communication, explanations of politeness values, positive reinforcement, and redirection of activities can significantly reduce the frequency of this behavior. The results of this study are supported by several literature reviews that highlight the importance of empathy, positive reinforcement, and a conducive learning environment in developing early childhood character. This article provides practical contributions for teachers, parents, and education stakeholders in effectively managing early childhood behavior, particularly in the school environment. The applied approach also strengthens the relationship between teachers and children, creates a comfortable and inclusive learning atmosphere, and increases children's awareness of social and moral values.